A Study of Psychological Well-being and Work–life Balance of Female Nurses - Anagha, L. Lavalekar; Kanchan, D. Pande (Indian Journal of Nursing Sciences, 2024)
Introduction: Women in nursing profession have multiple personal and professional responsibilities and challenges like giving priority to family along with financial security. Aim: This study aims to study psychological well-being (PWB) and work–life balance (WLB) of female nurses. Methodology: Sample consists of 163 women nurses (incidental sampling) within Pune district. Tools: WLB Research (Dr. S. Singh) with four dimensions - work spillover in personal life, personal life spillover in work (PLSW), work/life behavioral enhancers, and work/life behavioral constrainers and Carol Ryff’s scale of PWB adapted by JPIP with six areas – Autonomy, environmental mastery (EM), personal growth, positive relations (PR), purpose in life (PIL), and self-acceptance. Results: It is observed that personal issues and stresses are spilling over their work life. Significant positive correlation was observed between WLB and PWB. Especially, personal relation with others, PIL, and EM has a significant PR with total WLB. Furthermore, work–life behavior enhancers show a decisive, PR with PWB. Conclusions: Nurses seem to experience personal issues influencing work (PLSW) to the highest as compared to other aspects of WL balance; however, no significant difference was seen in any of the parameter across age group on W–L balance or PWB.